2019
DOI: 10.1073/pnas.1907418116
|View full text |Cite
|
Sign up to set email alerts
|

Long-range Pitx2c enhancer–promoter interactions prevent predisposition to atrial fibrillation

Abstract: Genome-wide association studies found that increased risk for atrial fibrillation (AF), the most common human heart arrhythmia, is associated with noncoding sequence variants located in proximity to PITX2. Cardiomyocyte-specific epigenomic and comparative genomics uncovered 2 AF-associated enhancers neighboring PITX2 with varying conservation in mice. Chromosome conformation capture experiments in mice revealed that the Pitx2c promoter directly contacted the AF-associated enhancer regions. CRISPR/Cas9-mediated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 47 publications
0
49
0
Order By: Relevance
“…These findings are consistent with other murine models of Pitx2 deficiency ( 10 12 ). In addition, recent findings in a mouse model that deactivated the enhancer region of Pitx2c found Bmp10 to be one of the most upregulated genes ( 37 ). These results suggest that a common repressor/enhancer transcriptional network may exist between Bmp10 and Pitx2 whereby the loss of one of these genes results in the reciprocal upregulation of the other ( 18 , 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…These findings are consistent with other murine models of Pitx2 deficiency ( 10 12 ). In addition, recent findings in a mouse model that deactivated the enhancer region of Pitx2c found Bmp10 to be one of the most upregulated genes ( 37 ). These results suggest that a common repressor/enhancer transcriptional network may exist between Bmp10 and Pitx2 whereby the loss of one of these genes results in the reciprocal upregulation of the other ( 18 , 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…In most cases, those AF associated variants are located in intergenic regions, limiting our understanding of the molecular mechanisms behind those associations. The exception to the rule is represented by 4q25 variants, to which several studies, including ours, have demonstrated a pivotal role regulating Pitx2 expression [ 228 , 229 , 230 ] as well as demonstrating a functional role for PITX2 in AF pathophysiology [ 130 , 133 , 134 , 154 ]. Thus, one of the future challenges in the genetics of AF is to discover the molecular mechanism behind GWAS data and AF pathophysiology [ 231 ], reemphasizing the responsibility of epigenetics.…”
Section: Perspectivesmentioning
confidence: 99%
“… 87 , 89 , 90 By demonstrating a functional connection between the upstream AF-associated variants, PITX2 expression, and predisposition to AF, a recent study by Zhang et al . 91 has now provided conclusive evidence for PITX2 being the causal gene at this locus. Specifically, they showed that AF risk variants located at 4q25 reside in genomic regions possessing long-range transcriptional regulatory function directed at PITX2 , and that the deletion of these genomic regions leads to reduced Pitx2c transcription and AF predisposition.…”
Section: From Gwas Locus To Gene and Mechanismmentioning
confidence: 97%
“…Specifically, they showed that AF risk variants located at 4q25 reside in genomic regions possessing long-range transcriptional regulatory function directed at PITX2 , and that the deletion of these genomic regions leads to reduced Pitx2c transcription and AF predisposition. 91 …”
Section: From Gwas Locus To Gene and Mechanismmentioning
confidence: 99%